Practical Application of ICT During Physics Lessons - Semków-Nędza, Beata (Journal of Education, Technology and Computer Science, 2022)
The constant changes taking place in society, digitization, the use of ever newer technological solutions, should also generate changes in the way knowledge is transmitted to students. The article presents examples of information and communication technology (ICT) tools used in physics lessons. The ways and advantages of using the modern ICT tools discussed are also presented. The use of modern ICT tools should facilitate the understanding of physical phenomena and concepts.